THE INFLUENCE OF ACCOUNTING INFORMATION SYSTEMS QUALITY ON INDIVIDUAL PERFORMANCE - Meiryani; Sudrajat, Jajat; Daud, Zaidi Mat; Isa, Sani Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
—Quality accounting information systems will produce quality accounting information. Quality accounting information helps users make decisions. A quality accounting information system can assist employees in carrying out their duties and authority so as to improve individual performance. The research problem examined is how much influence the quality of accounting information systems on individual performance. The purpose of this study is to seek the truth through testing the influence of a quality accounting information system on individual performance. The results of the study are expected to be evidence that the model offered can be a solution to the problem of accounting information system quality and individual performance by management. The data used were obtained through a survey by distributing questionnaires, processed statistically using multiple linear regression. The results of this study indicate that individual performance can be improved by a quality accounting information system.